2015
DOI: 10.1148/radiol.2015142215
|View full text |Cite
|
Sign up to set email alerts
|

Can Quantitative CT Texture Analysis be Used to Differentiate Fat-poor Renal Angiomyolipoma from Renal Cell Carcinoma on Unenhanced CT Images?

Abstract: CT texture analysis can be used to accurately differentiate fp-AML from RCC on unenhanced CT images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 232 publications
(159 citation statements)
references
References 40 publications
5
151
1
2
Order By: Relevance
“…The one case of bilateral angiomyolipoma was diagnosed as tuberous sclerosis after further investigations of other systems by different imaging modalities. Our findings correlate well with the findings of Taryn Hodgdon et al, 3 who found the mean age of RCC and AML was 59 +/-13 years and 53 +/-12, whereas in our study it was 60.03 years and 37.3 years. Verhoest G et al 4 in their study have found that the incidence of renal cell carcinoma was 6% in < 40 years, 38.5% in 40 -60 years, 52.3% in 60 -80 years and 3.2% in > 80 years.…”
Section: Discussionsupporting
confidence: 93%
“…The one case of bilateral angiomyolipoma was diagnosed as tuberous sclerosis after further investigations of other systems by different imaging modalities. Our findings correlate well with the findings of Taryn Hodgdon et al, 3 who found the mean age of RCC and AML was 59 +/-13 years and 53 +/-12, whereas in our study it was 60.03 years and 37.3 years. Verhoest G et al 4 in their study have found that the incidence of renal cell carcinoma was 6% in < 40 years, 38.5% in 40 -60 years, 52.3% in 60 -80 years and 3.2% in > 80 years.…”
Section: Discussionsupporting
confidence: 93%
“…A potential discriminating feature on CT that was not assessed in our study is lesion homogeneity. Previous studies using subjective analysis have demonstrated that AML without visible fat were significantly more homogeneous than RCC [18,25], and more recently, Hodgdon et al showed similar findings using quantitative texture analysis [34]. The use of homogeneity combined with other CT imaging findings for diagnosis of AML without visible fat requires further study, but may be of particular utility in AML without visible fat that are iso-attenuating.…”
Section: Discussionmentioning
confidence: 90%
“…Because traditional visual inspection of images might not allow for recognizing subtle differences in textural information, the application of TA has the potential to further enhance the diagnostic and prognostic value of imaging. The increase of interest in evaluating TA in radiology is reflected by recent literature describing potential applications of the technique in oncologic (11)(12)(13), neuroradiologic (14), musculoskeletal (15,16), and lung imaging (17). To our knowledge, only one preliminary study, published as a conference abstract, has evaluated the potential of TA for cardiac MR imaging so far (18).…”
Section: Cardiac Mr Imaging Data Acquisitionmentioning
confidence: 99%